2022
DOI: 10.1523/eneuro.0080-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

Volume and Connectivity Differences in Brain Networks Associated with Cognitive Constructs of Binge Eating

Abstract: Alerts: Sign up at www.eneuro.org/alerts to receive customized email alerts when the fully formatted version of this article is published.1. Volume and connectivity differences in brain networks associated with cognitive constructs of binge eating 2. Brain network differences in binge eating

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 223 publications
(572 reference statements)
2
6
0
4
Order By: Relevance
“…Our current findings are consistent with our hypothesis that BED and BN commonly have weak FC between the lateral OFC and inhibitory control-related regions. This is also consistent with previous studies indicating that BED and BN have weakened FC between frontal regions related to cognitive control [ 10 ]. In this study, lateral OFC-DLPFC FC did not show a significant correlation with impulsivity in both BED and BN groups.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our current findings are consistent with our hypothesis that BED and BN commonly have weak FC between the lateral OFC and inhibitory control-related regions. This is also consistent with previous studies indicating that BED and BN have weakened FC between frontal regions related to cognitive control [ 10 ]. In this study, lateral OFC-DLPFC FC did not show a significant correlation with impulsivity in both BED and BN groups.…”
Section: Discussionsupporting
confidence: 93%
“…Additional effort has been made to elucidate the neurobiological pathophysiology underlying these clinical differences between BED and BN. For instance, previous functional magnetic resonance imaging (fMRI) studies using behavioral tasks have suggested that these two diseases differ in reward processing [ 10 ]. BED and BN have also been found to show different brain activation patterns in relation to reward processing [ 11 ], as well as different reward sensitivity in related brain regions [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies focusing their investigation on binge eating using tasks that probe reward responsiveness specifically for food, find a higher activity of the OFC, ACC as well as striatum during the anticipation and receipt of high-energy-density food, compared with lower activity during the anticipation and receipt of money [16,17]. This is in line with structural data, finding higher volumes in cortical areas, as well as NAc [18 ▪ ,19 ▪ ]. Interestingly, patients with bulimia nervosa may have even higher OFC volume and activation of ACC during food anticipation compared with BED [11,20].…”
Section: Neuroimaging Findings Related To Reward Processing In Binge ...supporting
confidence: 59%
“…The ILA is also critical when suppression of behavioral action (lever pressing) is required to obtain a sucrose pellet reward (Capuzzo and Floresco 2020). Similar function was highlighted in a recent integrative review of brain network differences in binge eating disorder (BED), where decreased activity in the medial PFC was linked to decreased cognitive control over food-related decisions in BED (Hartogsveld et al 2022). In this regard, ORX signaling within the ventromedial PFC is required in an animal model of cognitive control of feeding.…”
Section: Medial and Lateral Prefrontal Cortexmentioning
confidence: 57%